Evaluating TAB2, IKBKB, and IKBKG Gene Polymorphisms and Serum Protein Levels and Their Association with Age-Related Macular Degeneration and Its Treatment Efficiency - Alvita Vilkeviciute; Enrika Pileckaite; Akvile Bruzaite; Dzastina Cebatoriene; Greta Gedvilaite-Vaicechauskiene; Loresa Kriauciuniene; Dalia Zaliuniene; Rasa Liutkeviciene (Medicina)
Background and Objectives: Age-related macular degeneration (AMD) is the leading cause of blindness, affecting millions worldwide. Its pathogenesis involves the death of the retinal pigment epithelium (RPE), followed by photoreceptor degeneration. Although AMD is multifactorial, various genetic markers are strongly associated with the disease and may serve as biomarkers for evaluating treatment efficacy. This study investigates TAB2 rs237025, IKBKB rs13278372, and IKBKG rs2472395 variants and their respective serum protein concentrations in relation to AMD occurrence and exudative AMD treatment response to anti-VEGF treatment. Materials and Methods: The case–control study involved 961 individuals, and they were divided into three groups: control, early AMD, and exudative AM patients. Genotyping of selected SNPs were conducted using a real-time polymerase chain reaction method (RT-PCR). Based on the clinical OCT and BCVA data, patients with exudative AMD were categorized into one of two groups: responders and non-responders. The data obtained were analyzed using the “IBM SPSS Statistics 29.0” software program. Results: Our study revealed that TAB2 rs237025 allele A was identified as a risk factor for early and exudative AMD development. The same associations remained only in females with exudative AMD but not in males, suggesting gender-specific pathogenetic pathways in exudative AMD. Analysis of IKBKB rs13278372 or serum IKBKB protein associations with early or exudative AMD occurrence in the Lithuanian population revealed no significant associations. On the other hand, we found that each A allele of IKBKB rs13278372 was associated with a worse response to anti-VEGF treatment (OR = 0.347; 95% CI: 0.145–0.961; p = 0.041). These results suggest a potential marker for future studies evaluating anti-VEGF treatment for exudative AMD patients. IKBKG rs2472395 was a protective variant for early AMD in males and for exudative AMD in females only. Also, IKBKG protein concentration was lower in exudative AMD relative to the control group (median (IQR): 0.442 (0.152) vs. 0.538 (0.337), p = 0.015). Moreover, exudative AMD patients who carry the GG genotype of IKBKG rs2472394 exhibited significantly reduced serum IKBKG concentrations compared to the controls (median (IQR): 0.434 (0.199) vs. 0.603 (0.335), p = 0.012), leading to the hypothesis that the IKBKG rs2472394 variant might play a role in protein concentration differences and exudative AMD development. Conclusions: Our study identified the TAB2 rs237025 allele A as a significant risk factor for both early and exudative AMD, with gender-specific associations observed in females with exudative AMD, suggesting distinct pathogenetic pathways. While IKBKB rs13278372 and serum IKBKB protein levels showed no significant association with AMD development, the A allele of IKBKB rs13278372 was associated with a worse response to anti-VEGF treatment, indicating its potential as a marker for treatment outcomes. Additionally, the IKBKG rs2472395 variant was found to be protective for early AMD in males and exudative AMD in females, and lower IKBKG protein levels were associated with exudative AMD, particularly in patients with the GG genotype of IKBKG rs2472394, suggesting its role in protein concentration and disease progression. These findings highlight genetic markers that may contribute to AMD pathogenesis and treatment response.